(untitled) (Journal of Buffalo Science, 2018)
This paper provides a short review of the scientific literature, focusing on recent advances on the most representative events from birth to weaning, with special emphasis on the behavior and welfare of buffalo calves during the phases of imprinting, suckling and allosucking, based on the differences and similarities reported with dairy and beef cattle. The similarities include the facts that all 3 are gregarious animals whose dams separate from the herd prior to parturition to facilitate dam-calf bonding, and that maternal care fosters the ingestion of colostrum by the young. These species are also precocial and rely on mother – young mutual recognition for calf survival. In particular, mothers develop a selective bonding with their young soon after parturition, although buffalo cows seem to be tolerant to alien claves and are often engaged in communal nursing. In buffaloes and cattle negative emotions are induced by the stress brought on by early maternal separation. However, buffalo calves are more prone to express cross-sucking and contract neonatal diseases with higher mortality rates in intensive systems as compared to cattle. The review concludes that all three exhibit similar behaviors from parturition to weaning although the knowledge about the specific needs of buffalo calves should be increased and appropriate management practices implemented to improve their welfare state.